PELATIHAN PENGGUNAAN APLIKASI CANVA UNTUK MEMBUAT BAHAN PEMBELAJARAN - Salsabila, Zulpa; Nuraina; Dika Lesmana, Ivan (Jurnal Berdaya Mandiri, 2023)
The teacher is a very important element in the educational process, where the teacher plays an important role in efforts to develop character and human resources who have competence in any field. SD Negeri 105335 Kebun Sayur is an educational unit with an elementary level in Tanjung Morawa B, Kec. Cape Morawa, Kab. Deli Serdang, North Sumatra. The problem currently experienced by teachers is the limitations in producing teaching materials, so that in carrying out teaching and learning activities SD Negeri 105335 Kebun Sayur is currently still using books only to convey learning material. Because they still use books, students are sometimes lazy to read the contents. The cause of the problems experienced by these teachers is due to the lack of understanding of teachers in using applications that can help them to make teaching materials, this is related to the lack of understanding of teachers using technology. teachers need knowledge in developing teaching materials both in the form of presentation slides or in the form of interactive videos with presentation media so that the learning process in schools can be carried out optimally and improve the ability of teachers to be creative in creating teaching materials using the Canva application. Teachers experienced increased knowledge and understanding after training on using the Canva application to create learning materials.  Keywords: Training, Presentations, Canva